Graded pore carbon / crystalline phase amorphous biphase metal phosphide composite electrocatalyst and preparation and application thereof
By introducing a graded pore carbon/crystalline biphasic metal phosphide composite structure into the carbon-based metal phosphide catalyst, the problems of stability and catalytic performance of the catalyst in an acid-base environment are solved, and an efficient electrocatalytic material suitable for full hydrolysis applications is achieved.
Patent Information
- Application Number
- CN202411841286.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing carbon-based metal phosphide water electrolytic catalysts are difficult to take into account both acid and alkali resistance, excellent HER and OER performance, and have poor stability, making them difficult to adapt to full hydrolysis applications.
The graded pore carbon/crystalline biphasic metal phosphide composite electrocatalyst is used to form the graded pore carbon substrate and crystal-amorphous biphasic metal phosphide material in situ through two-stage gradient treatment and quenching treatment of molten salt, carbon source, transition metal source, phosphorus source and additive.
It realizes the acid and alkali resistance of the catalyst and excellent HER and OER performance, which are suitable for full hydrolysis applications and improves the stability of the material.
Smart Images

Figure CN119663351A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic materials, and in particular to the field of water electrolysis catalyst materials. Background Art
[0002] Water electrolysis is an electrochemical process that decomposes water into hydrogen (H2) and oxygen (O2) through electrical energy. It is considered to be an effective way to achieve renewable energy storage and utilization. The process includes two main electrochemical reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). However, both reactions require efficient electrocatalysts to reduce the overpotential of the reaction, improve the energy conversion efficiency and reaction rate, and thus achieve more economical and efficient hydrogen production. Although traditional electrocatalysts such as precious metals (such as platinum, iridium, etc.) show excellent catalytic performance, their large-scale application is limited by their high cost and rarity. Precious metal catalysts are not only expensive, but also have limited reserves on earth, which cannot meet the needs of large-scale industrial applications in the future. Therefore, the development of efficient, low-cost and stable electrocatalysts has become the focus of current research.
[0003] In this context, transition metal-based catalysts, especially transition metal phosphides (such as cobalt phosphide, nickel phosphide and iron phosphide), have attracted widespread attention due to their low cost, abundant reserves and excellent electrocatalytic performance.
[0004] The prior art also provides some technologies in this regard. For example, the Chinese patent document with publication number CN115458753A discloses a method for preparing a composite bifunctional electrocatalyst and its use in high-power zinc-air batteries. The catalyst is a composite material composed of a nickel-iron hydrotalcite precursor obtained by chemical bath deposition, annealed and phosphated to form Ni2P / Fe2P heterogeneous phosphide and anion-doped hollow carbon spheres. The composite catalyst can obtain good OER performance.
[0005] For another example, a Chinese patent document with publication number CN116078412A discloses a composite material with a heterogeneous structure, which includes phosphated graphene as a carrier and cobalt-iron phosphide supported on the carrier, wherein the phosphated graphene is in a foamy state, the cobalt-iron phosphide is in a cubic particle state, and a heterogeneous structure is formed between the phosphated graphene and the cobalt-iron phosphide. The material has an excellent catalytic effect in both electrochemical hydrogen evolution and / or oxygen evolution reactions, and can be used for the selectivity of 5-hydroxymethylfurfural oxidation to generate furandicarboxylic acid.
[0006] In addition, a Chinese patent document with publication number CN113772644A discloses a bimetallic phosphide, a preparation method and an application thereof. The preparation method of the bimetallic phosphide comprises the following steps: coprecipitating potassium ferrocyanide and a cobalt salt to prepare iron-cobalt Prussian blue; and then phosphating the iron-cobalt Prussian blue under a protective atmosphere to prepare a bimetallic phosphide.
[0007] In summary, the prior art discloses some carbon-based non-silicon metal phosphide electrocatalytic materials, but these materials have difficulty in taking into account the acid and alkali resistance issues, and also have difficulty in taking into account the effects of HER and OER, are difficult to adapt to full hydrolysis applications, and have poor stability. Summary of the invention
[0008] In view of the insufficient performance of existing carbon-based metal phosphide water electrolysis catalysts, the first purpose of the present invention is to provide a method for preparing a graded porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst, aiming to prepare a new material that can tolerate acid and alkali and has excellent OER and HER performance and is suitable for full hydrolysis application requirements.
[0009] The second object of the present invention is to provide a hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method.
[0010] The third object of the present invention is to provide an application of the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst for water electrolysis.
[0011] The fourth object of the present invention is to provide a water electrolysis device containing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst for water electrolysis.
[0012] A method for preparing a graded porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst comprises pre-insulating a mixed raw material comprising a molten salt, a carbon source, a transition metal source, a phosphorus source and an additive at a temperature T1 for a first stage, then heating the mixed raw material to a temperature T2 and performing a second stage of insulation to obtain a precursor material; and quenching the precursor material to obtain the graded porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst.
[0013] The auxiliary agent is a compound containing two or more acidic groups; the acidic groups include at least one of a carboxylic acid group and a phosphoric acid group;
[0014] The temperature T1 is 200-450°C; the temperature T2 is 850-1200°C.
[0015] The present invention innovatively performs the two-stage gradient treatment of transition metal source, phosphorus source and carbon source with the aid of molten salt and additives, and further cooperates with subsequent rapid cooling treatment, so that a graded porous carbon substrate can be formed in situ, and the crystalline-amorphous dual-phase metal phosphide material can be grown in situ on the substrate. Studies have shown that the material prepared by the preparation method of the present invention has excellent acid and alkali resistance, and takes into account excellent and stable HER and OER performance, and can be suitable for full hydrolysis applications.
[0016] In the present invention, the molten salt includes at least one of sodium chloride, potassium chloride, potassium nitrate, sodium carbonate, ammonium nitrate, calcium fluoride, magnesium fluoride, and aluminum fluoride; preferably two or more; further, it can be a composite molten salt of sodium chloride and potassium nitrate (the weight ratio of the components in the composite molten salt can be 0.1 to 10:1). Studies have shown that the use of the combined molten salt can help further synergistically enhance the synergy of the two-stage gradient insulation-quenching process described in the present invention, help further optimize the crystal, amorphous behavior and composite interface of the prepared material, and help further improve its HER and OER performance.
[0017] In the present invention, the carbon source includes at least one of inorganic carbon and organic carbon source. The organic carbon source includes at least one of monosaccharide compound, disaccharide compound, polysaccharide and polymer. The inorganic carbon includes at least one of graphite phase carbon nitride and graphene oxide. The monosaccharide includes glucose. The disaccharide includes sucrose. The carbon source includes at least one of starch and lignin. The polymer includes PVP.
[0018] Preferably, the carbon source includes polysaccharides and polymers (the ratio of the two can be 1 to 5:1). The present invention shows that the preferred carbon source and the molten salt-two-stage gradient roasting-quenching combined process of the present invention can further achieve synergy, help to further optimize the physical and chemical structure of the prepared material, and help to further enhance the HER and OER performance of the prepared material.
[0019] In the present invention, the transition metal element in the transition metal source can be any transition metal element known in the industry that can be used for electrocatalysis. Preferably, the transition metal source contains two or more transition metal elements. Considering the effect and cost, it can include two or more of iron, nickel and cobalt.
[0020] In the present invention, the phosphorus source may be any component that can provide the P element. Considering the material cost, it may be at least one of calcium hydrogen phosphate, potassium dihydrogen phosphate, superphosphate and ammonium phosphate.
[0021] In the present invention, the auxiliary agent includes at least one of phytic acid, oxalic acid and citric acid.
[0022] In the present invention, the weight ratio of the transition metal source (calculated as transition metal element), molten salt, carbon source and additive is 1:2-5:5-15:0.5-3, and can further be 1:2.5-4.5:5-10:1-2; wherein the molar ratio of transition metal element / P element in the transition metal source and phosphorus source is 1:0.2-2 (and can further be 1:1-1.5).
[0023] In the present invention, the mixed raw material is obtained by mixing molten salt, carbon source, transition metal source, phosphorus source and auxiliary agent in liquid phase and then desolvating. The desolvation means is spraying.
[0024] In the present invention, the treatment atmosphere of the first and second heat preservation stages is a protective atmosphere, and may further be a hydrogen-containing atmosphere. The hydrogen-containing atmosphere is, for example, a mixed gas containing hydrogen and an inert gas, wherein the content of hydrogen is, for example, 1 to 10% by volume.
[0025] In the present invention, the temperature of the first stage of heat preservation is 250-350°C.
[0026] Preferably, the insulation time of the first insulation stage is 1 to 5 hours, and can further be 2 to 3 hours.
[0027] In the present invention, the temperature of the second insulation stage is 900-1050°C.
[0028] Preferably, the second insulation period has an insulation time of 1 to 5 hours, and may further be 2 to 3 hours.
[0029] The cooling medium selected in the quenching stage is a liquid medium with a temperature below 30°C; preferably water or liquid nitrogen. The present invention shows that the use of the liquid nitrogen as a quenching medium, combined with other components and processes, can obtain a better process synergy effect, and can further enhance the acid and alkali resistance and HER and OER performance of the prepared material.
[0030] In the present invention, during the rapid cooling stage, the temperature difference between the precursor material and the rapid cooling medium when in contact is above 500°C, and can further be 850-1200°C.
[0031] In the present invention, the second stage heat-insulated material can be placed in a quenching medium while hot, and the material is in direct contact with the quenching medium for quenching treatment.
[0032] The present invention further includes a step of carbon coating the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst. The carbon coating step may be conventional, for example, the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst may be carbonized after being composited with a carbon source.
[0033] The present invention also provides a hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method.
[0034] In the present invention, the preparation method can give the prepared material special physical and chemical characteristics, for example, it can be combined with the synchronous construction of a hierarchical porous carbon substrate and the in-situ synchronous growth of a crystalline-amorphous composite technical phosphide on the substrate. The material prepared by the present invention has the advantages of acid and alkali resistance and excellent HER and OER performance.
[0035] The present invention also provides an application of the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method, which is used as a catalytic material for electrocatalysis of water.
[0036] In the present invention, the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst described in the present invention can be used as a catalyst, and water electrocatalysis can be performed based on conventional water electrolysis means and principles.
[0037] The present invention also provides a hydrocatalytic device, which comprises the hierarchical pore carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method or is prepared by the hierarchical pore carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst.
[0038] The hydroelectric catalytic device of the present invention, in addition to comprising the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst of the present invention, other components and structural parts may be known.
[0039] Beneficial effects:
[0040] The present invention innovatively subjects the transition metal source, phosphorus source and carbon source to the two-stage gradient treatment with the assistance of molten salt and additives, and further cooperates with subsequent rapid cooling treatment, so that the catalytic material with the physicochemical characteristics can be formed in situ, and the catalytic material has excellent acid and alkali resistance, and has excellent HER and OER performance, can be suitable for full hydrolysis applications, and improves its stability.
[0041] For example, the material described in the present invention has a HER potential in an alkaline system that can be reduced to 69 mV, an OER potential that can be reduced to 1.455 V, and a total hydrolysis potential that can be reduced to 1.545 V. Compared with other carbon-based metal phosphide materials, it has excellent HER and OER performances. In addition, it can also obtain excellent HER and OER performances in an acidic system. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is the alkaline water decomposition stability diagram of the material prepared in Example 1;
[0043] Figure 2 The acidic water decomposition stability diagram of the material prepared in Example 1;
[0044] Figure 3 This is the SEM image of the material prepared in Example 1. DETAILED DESCRIPTION
[0045] The present invention provides an exemplified method for preparing a crystalline-amorphous dual-phase metal phosphide electrocatalyst, the steps of which are, for example: fully mixing and dispersing the molten salt, carbon source, metal source, and phosphorus source in an additive solution S, and spray drying; then calcining the mixture in two stages; placing the mixture in cold water or liquid nitrogen for rapid cooling while hot, and finally washing the mixture with water to obtain the water electrolysis material.
[0046] The molten salt contains at least one of sodium chloride, potassium chloride, potassium nitrate, sodium carbonate, ammonium nitrate, calcium fluoride, magnesium fluoride and aluminum fluoride.
[0047] The carbon source includes at least one of graphite-phase carbon nitride, graphene oxide, glucose, sucrose, starch and lignin, and is preferably a mixture of the above carbon sources and PVP.
[0048] The metal source includes one or more nitrates of iron, nickel and cobalt, preferably a mixture of the above nitrates and potassium cobalt cyanide.
[0049] The phosphorus source comprises at least one of calcium hydrogen phosphate, potassium dihydrogen phosphate, superphosphate and ammonium phosphate.
[0050] The auxiliary agent solution S is a solution containing one or more of phytic acid, oxalic acid, citric acid, etc., and the concentration of the solution is 0.05-0.5M.
[0051] The gradient calcination process includes a first calcination process at a temperature T1 and a second calcination process at a temperature T2; wherein the temperature T1 is 200-450°C; the temperature T2 is 850-1200°C;
[0052] The following is a more specific implementation method:
[0053] The weight of the transition metal source is based on the weight of the transition metal element therein.
[0054] Example 1
[0055] Step (1): Premixing
[0056] A transition metal source (a mixture of iron nitrate, nickel nitrate and potassium cobalt cyanide with a mass ratio of 0.5:0.2:1 for Fe / Ni / Co), a molten salt (sodium chloride and potassium nitrate with a mass ratio of 1:0.5 for Na / K), a carbon source (a mixture of lignin and PVP with a mass ratio of 1.5:0.5) and a phosphorus source (calcium hydrogen phosphate and potassium dihydrogen phosphate with a mass ratio of 1:0.3; the molar ratio of the metal element in the metal source to the P in the phosphorus source is 1:1) with a mass ratio of 1:3:6 were ground for 10 minutes; then added to a solution S containing an additive (a mixed solution of 0.05M phytic acid and 0.2M oxalic acid) (the mass ratio of the additive to the metal source is 1:2), stirred for 10 minutes, and finally spray-dried to obtain a mixture X;
[0057] Step (2): Gradient calcination-quenching
[0058] The mixture X obtained in step (1) is placed in a tube furnace, and an inert atmosphere of 5v% H2 / Ar is introduced to fill the tube with the inert atmosphere until it is saturated. The temperature is increased to 250°C (marked as T1) at a heating rate of 5°C / min, and kept at this temperature for 2h (marked as t1). The temperature is then increased to 950°C (sintering temperature T2) at a heating rate of 5°C / min, and then kept at this temperature for 3h (marked as t2). The mixture is then poured into liquid nitrogen while hot for rapid cooling to obtain component F.
[0059] Step (3): Washing
[0060] The component F obtained in step (2) was mixed with water at a mass ratio of 1:100, stirred vigorously for 10 minutes, and filtered, and repeated three times to obtain a water electrolysis catalyst material (active material, also marked as HPC-CAMP)
[0061] Example 2
[0062] Compared with Example 1, the only difference is that the type of molten salt is changed. The experimental groups are:
[0063] Group A: The molten salt is sodium chloride;
[0064] Group B: molten salt is potassium nitrate;
[0065] The total weight of the molten salt and other operating conditions are the same as those in Example 1, and the test is carried out in the manner of Example 1. The results are shown in Table 1.
[0066] Example 3
[0067] Compared with Example 1, the only difference is that the type of carbon source is changed. The experimental groups are:
[0068] Group A: The carbon source was glucose;
[0069] Group B: carbon source is lignin;
[0070] Group C: carbon source was PVP;
[0071] The total weight of the carbon source and other operating conditions are the same as those in Example 1, and the test is carried out in the same manner as in Example 1. The results are shown in Table 1.
[0072] Example 4
[0073] Compared with Example 1, the only difference is that the type of metal source is changed. The experimental groups are:
[0074] Group A: The metal source is a mixture of ferric nitrate and potassium cobalt cyanide, and the ratio of iron to cobalt and the weight of the total metal elements are the same as those in Example 1;
[0075] Group B: The metal source is a mixture of nickel nitrate and potassium cobalt cyanide, and the ratio of nickel to cobalt and the weight of the total metal elements are the same as in Example 1;
[0076] The weight of the metal source and other operating conditions are the same as those in Example 1, and the test is carried out in the manner of Example 1. The results are shown in Table 1.
[0077] Example 5
[0078] Compared with Example 1, the only difference is that the type of solution S is changed. The experimental groups are:
[0079] Group A: Solution S is 0.25 M phytic acid solution;
[0080] Group B: Solution S is 0.25 M oxalic acid solution;
[0081] The total weight of the additives and other operating conditions are the same as those in Example 1, and the test is carried out in the same manner as in Example 1. The results are shown in Table 1.
[0082] Example 6
[0083] Compared with Example 1, the only difference is that in step 2, the quenching medium is deionized water at a temperature of 25° C., and the other operations and parameters are the same as those in Example 1.
[0084] Example 7
[0085] Compared with Example 1, the only difference is that in step 1, the weight ratio of the transition metal source, the molten salt, and the carbon source is 1:4:10; the molar ratio of the metal element in the metal source to the P in the phosphorus source is 1:1.5; the mass ratio of the additive to the metal source is 1:1. In step 2, the atmosphere is a 3v% H2 / Ar inert atmosphere, the temperature T1 is 350°C, the holding time is 3h; the temperature T2 is 1000°C, the holding time is 2h; the furnace is cooled to 850°C and then quenched while hot, and other operations and parameters are the same as in Example 1.
[0086] Comparative Example 1
[0087] Compared with Example 1, the only difference is that in step (1), no molten salt is added, and other operations and parameters are the same as Example 1.
[0088] Comparative Example 2
[0089] Compared with Example 1, the only difference is that in step (1), the solution S is water, and no auxiliary solute is added thereto. Other operations and parameters are the same as in Example 1.
[0090] Comparative Example 3
[0091] Compared with Example 1, the only difference is that step (2) is not performed and the two-stage gradient roasting treatment is not performed, that is, the temperature of T1 is set to be the same as T2, and the other operations and parameters are the same as Example 1.
[0092] Comparative Example 4
[0093] Compared with Example 1, the only difference is that in step (2), no rapid cooling quenching is performed, but natural cooling is performed at room temperature after roasting. Other operations and parameters are the same as in Example 1.
[0094] Material electrochemical performance test:
[0095] The catalytic performance was tested in a three-electrode system using a rotating disk electrode, the HPC-CAMP as a working electrode, mercuric oxide (alkaline) or a saturated calomel electrode (acidic) as a reference electrode, and a platinum electrode as a counter electrode.
[0096] Catalytic performance test under alkaline conditions: In 1 M KOH system, the HER reaction at a current density of 10 mA cm -2 The overpotential (η j=10 ) is 69.4 mV; the OER reaction is at a current density of 10 mA cm -2 The potential under j=10 ) is 1.455V. The final product is coated on nickel foam as cathode and anode, and the electrolyte is also 1M KOH solution. The water electrolysis performance is tested and reaches 10mA cm -2 The water splitting current density only requires a potential of 1.545V;
[0097] Catalytic performance test under acidic conditions: In 0.5M H2SO4 system, the HER reaction was carried out at a current density of 10mAcm -2 The overpotential (η j=10 ) is 52.1 mV; the OER reaction is at a current density of 10 mA cm -2 The potential under j=10) is 1.432V. The final product is coated on nickel foam as cathode and anode, and the electrolyte is also 1M KOH solution. The water electrolysis performance is tested and reaches 10mAcm -2 The water decomposition current density only requires a potential of 1.536 V. The results are shown in Table 1:
[0098] Table 1
[0099]
[0100] It can be seen from Table 1 that based on the embodiments and comparative examples 1 to 4, the process can obtain electrocatalytic materials that are resistant to acid and alkali and have excellent HER and OER performance. In addition, it can be seen from Examples 1 and 2 that the use of the combined molten salt described in the present invention, combined with the process of the present invention, can obtain better synergy and better synergistic performance. In addition, it can be seen from Examples 1, 3 to 5 that the use of the preferred carbon source, preferred metal source and preferred additives described in the present invention can also enhance technical synergy and further optimize the performance of the material. It can be seen from Examples 1 and 6 that the use of liquid nitrogen for rapid cooling can help to further optimize the physicochemical structure of the material and obtain better electrocatalytic activity.
Claims
1. A method for preparing a hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst, characterized in that: A mixed raw material including molten salt, carbon source, transition metal source, phosphorus source and additive is pre-heated at temperature T1 for a first stage, then heated to temperature T2 and heat-treated for a second stage to obtain a precursor material; the precursor material is quenched to obtain the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst; The auxiliary agent is a compound containing two or more acidic groups; the acidic groups include at least one of a carboxylic acid group and a phosphoric acid group; The temperature T1 is 200-450°C; the temperature T2 is 850-1200°C.
2. The method for preparing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst according to claim 1, characterized in that: The molten salt includes at least one of sodium chloride, potassium chloride, potassium nitrate, sodium carbonate, ammonium nitrate, calcium fluoride, magnesium fluoride, and aluminum fluoride; preferably two or more.
3. The method for preparing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst according to claim 1, characterized in that: The carbon source includes at least one of inorganic carbon and organic carbon source; Preferably, the organic carbon source includes at least one of monosaccharide compounds, disaccharide compounds, polysaccharides and polymers.
4. The method for preparing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst according to claim 1, characterized in that: The transition metal source contains two or more transition metal elements, preferably two or more of iron, nickel and cobalt; Preferably, the phosphorus source is at least one of calcium hydrogen phosphate, potassium dihydrogen phosphate, superphosphate and ammonium phosphate; Preferably, the auxiliary agent includes at least one of phytic acid, oxalic acid and citric acid; Preferably, the weight ratio of the transition metal source, molten salt, carbon source and additive is 1:2-5:5-15:0.5-3; wherein the molar ratio of transition metal element / P element in the transition metal source and phosphorus source is 1:0.2-2; Preferably, the mixed raw material is obtained by mixing molten salt, carbon source, transition metal source, phosphorus source and additive in liquid phase and then desolvating; Preferably, the desolventizing means is spraying.
5. The method for preparing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst according to claim 1, characterized in that: The first stage of heat preservation has a heat preservation time of 1 to 5 hours; Preferably, the second insulation period has an insulation time of 1 to 5 hours.
6. The method for preparing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst according to claim 1, characterized in that: The cooling medium selected in the rapid cooling stage is a liquid medium with a temperature below 30°C; preferably water or liquid nitrogen.
7. The method for preparing the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst according to claim 1 or 6, characterized in that: In the quenching stage, the temperature difference between the precursor material and the quenching medium when in contact is above 500°C; Preferably, the method further comprises the step of carbon coating the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst.
8. A hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It is used as a catalytic material for the electrocatalysis of water.
10. A hydroelectric catalytic device, characterized in that: The invention comprises a hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst prepared by the preparation method according to any one of claims 1 to 7 or is prepared by the hierarchical porous carbon / crystalline amorphous dual-phase metal phosphide composite electrocatalyst.
Citation Information
Patent Citations
Bimetallic phosphide as well as preparation method and application thereof
CN113772644A
Preparation method of composite difunctional electrocatalyst and application of composite difunctional electrocatalyst in high-power zinc-air battery
CN115458753A
Composite material with heterostructure as well as preparation method and application of composite material
CN116078412A
Preparation method and application of nitrogen and phosphorus codoped porous carbon plate / transition metal phosphide composite
CN109569683A
KR20240178061A
Cited By
Difunctional electro-catalytic water decomposition material as well as preparation and application thereof
CN120666390A
Bifunctional electrocatalytic water-splitting materials, preparation and use thereof
CN120666390B
